steel plate

JP7939611B1Active Publication Date: 2026-10-22NIPPON STEEL CORPORATION
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2026525245
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2025-03-31
Filing Date
2026-03-30
Publication Date
2026-10-22
Estimated Expiration
2046-03-30

Smart Images

  • Figure 0007939611000001
    Figure 0007939611000001
  • Figure 0007939611000002
    Figure 0007939611000002
Patent Text Reader

Abstract

In mass%, having a chemical composition comprising Ni: 0.010 to 1.000%, Cu: 0.010 to 1.000%, and Sn: 0.003 to 1.000%, and in analysis by X-ray photoelectron spectroscopy, the Sn content I at a position 1 nm deep from the surface sn1 and the Sn content I at a position 200 nm deep from the surface sn2 satisfy the following formula 1a, and in analysis by X-ray fluorescence spectrometry, the S intensity I at the surface s1 and the S intensity I at the 1 / 4 thickness position of the steel sheet s4 satisfy the following formula 2a, the steel sheet is provided. I sn1 / I sn2 ≤ 3.0 ···1a I s1 / I s4 ≥ 2.0 ···2a
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This disclosure relates to steel plates. [Background technology]

[0002] It is known that improving the chemical treatment properties of steel sheets is effective in improving the adhesion of coatings to steel sheets.

[0003] In this regard, Patent Document 1 describes a hot-rolled steel sheet having sulfides on its surface, with a sulfur content of 0.05 mg / m² per side. 2 A hot-rolled steel sheet characterized by having the above features is described. Furthermore, Patent Document 1 teaches that, according to the above configuration, a chemical conversion coating that serves as a base for painting the hot-rolled steel sheet is formed uniformly and densely.

[0004] Patent Document 2 describes a cold-rolled steel sheet containing, by mass%, C: 0.05-0.25%, Si: 0.8-2.4%, Mn: 1.0-3.0%, P: 0.10% or less, Al: 0.01-0.10%, with the remainder being Fe and unavoidable impurities. After continuous annealing, the sheet is pickled for 5-30 seconds in a pickling solution containing sulfur compounds at 20-80°C to form metal sulfides on the surface of the steel sheet, resulting in a sulfur content of 0.5-100 mg / m². 2 A method for manufacturing high-tensile cold-rolled steel sheets, characterized by the attachment of sulfides, is described. Furthermore, Patent Document 2 teaches that by utilizing a light pickling facility installed in a continuous annealing line to remove temper color (a thin surface oxide film) formed during annealing, and by including a sulfur compound in the pickling solution of this light pickling facility, the chemical conversion treatment properties of high-tensile cold-rolled steel sheets can be improved, and the corrosion resistance after painting can be greatly improved. [Prior art documents] [Patent Documents]

[0005] [Patent Document 1] Japanese Patent Publication No. 2003-277959 [Patent Document 2] Japanese Patent Publication No. 2007-231311 [Overview of the project] [Problems that the invention aims to solve]

[0006] For example, Patent Document 2 teaches that when the Si content of a steel sheet is high, Si oxides tend to form on the surface of the steel sheet during annealing, and these Si oxides inhibit the etching reaction on the surface of the steel sheet during chemical conversion treatment, degrading the chemical conversion treatment properties of the steel sheet after annealing. Now, the present inventors have found that when a steel sheet contains three elements, Ni, Cu, and Sn, the chemical conversion treatment properties of the steel sheet may decrease after annealing. Furthermore, generally, when the chemical conversion treatment properties decrease, areas where a chemical conversion treatment film has not been formed, such as what is called "skew," may occur, and as a result, the adhesion of the coating may decrease.

[0007] Therefore, the object of this disclosure is to provide a steel sheet containing Ni, Cu, and Sn that can exhibit improved coating adhesion. [Means for solving the problem]

[0008] To achieve the above objective, the inventors focused on the elemental distribution on the surface portion of the steel sheet and conducted investigations. As a result, the inventors discovered that by increasing the amount of sulfur (S) on the surface portion of the steel sheet and, relatedly, limiting the amount of sulfur (Sn) on the surface portion to a predetermined range, the adhesion of the coating on the steel sheet can be significantly improved, thus completing the technology of this disclosure.

[0009] The technology disclosed herein that has achieved the above objectives is as follows: (1) In mass%, Ni: 0.010~1.000%, Cu: 0.010~1.000%, and It has a chemical composition containing Sn: 0.003 to 1.000%, In analysis by X-ray photoelectron spectroscopy, the amount of Sn at a depth of 1 nm from the surface was sn1and the Sn amount I at a depth of 200 nm from the surface sn2 satisfies the following Formula 1a, in the analysis by the X-ray fluorescence analysis method, the S intensity I at the surface s1 and the S intensity I at the 1 / 4 thickness position of the steel sheet s4 satisfies the following Formula 2a, the steel sheet. I sn1 / I sn2 ≦3.0 ···1a I s1 / I s4 ≧2.0 ···2a (2) In the analysis by the X-ray photoelectron spectroscopy, the Sn amount I at a depth of 1 nm from the surface sn1 and the Sn amount I at a depth of 200 nm from the surface sn2 satisfies the following Formula 1b, the steel sheet according to the above (1). I sn1 / I sn2 ≦2.0 ···1b (3) In the analysis by the X-ray fluorescence analysis method, the S intensity I at the surface s1 and the S intensity I at the 1 / 4 thickness position of the steel sheet s4 satisfies the following Formula 2b, the steel sheet according to the above (1) or (2). I s1 / I s4 ≧3.0 ···2b (4) In the analysis by the X-ray photoelectron spectroscopy, the amounts of Sn, C, O, Fe, Mn, Si, Cu and Ni at a depth of 1 nm from the surface satisfy the following Formula 3a, the steel sheet according to any one of the above (1) to (3). Sn / (C+O+Fe+Mn+Si+Cu+Ni)≦0.010 ···3a provided that Sn, C, O, Fe, Mn, Si, Cu and Ni are the respective element contents in unit of at%. (5) In the analysis by the X-ray photoelectron spectroscopy, the amounts of Sn, C, O, Fe, Mn, Si, Cu and Ni at a depth of 1 nm from the surface satisfy the following Formula 3b, the steel sheet according to the above (4). Sn / (C+O+Fe+Mn+Si+Cu+Ni)≦0.007 ···3b However, the values ​​for Sn, C, O, Fe, Mn, Si, Cu, and Ni are given as at% for each element. (6) The chemical composition is, in mass%, Ni: 0.040~1.000%, Cu: 0.040~1.000%, and Sn: 0.004~1.000% A steel plate according to any one of the above items (1) to (5), characterized by including the following. (7) A steel plate according to any one of the above items (1) to (6), characterized by having a Vickers hardness of 190 Hv or more. [Effects of the Invention]

[0010] According to this disclosure, it is possible to provide a steel sheet containing Ni, Cu, and Sn that can exhibit improved coating adhesion. [Modes for carrying out the invention]

[0011] <Steel plate> According to one embodiment, the steel plate is, by mass %, Ni: 0.010~1.000%, Cu: 0.010~1.000%, and It has a chemical composition containing Sn: 0.003 to 1.000%, In analysis by X-ray photoelectron spectroscopy, the amount of Sn at a depth of 1 nm from the surface was sn1 and the amount of Sn at a depth of 200 nm from the surface I sn2 The following equation 1a is satisfied, In analysis by X-ray fluorescence analysis, the surface S intensity I s1 and S strength I at the 1 / 4 plate thickness position s4 A steel plate characterized by satisfying the following formula 2a. I sn1 / I sn2 ≤3.0 ···1a I s1 / I s4 ≥2.0 ···2a

[0012] It is unnecessary to impart chemical conversion treatment properties to cold-rolled steel sheets intended to be used as the base material for hot-dip galvanized steel sheets. However, for cold-rolled steel sheets intended for coating (not as the base material for hot-dip galvanized steel sheets, but on their surface), there is a need to impart chemical conversion treatment properties (for example, to improve coating adhesion). For example, as mentioned earlier, generally, if chemical conversion treatment properties decrease, areas where a chemical conversion coating, such as a "skew," has not formed may occur, resulting in reduced coating adhesion. Specifically, elements such as Sn are thought to inhibit the formation of a chemical conversion coating when concentrated on the steel sheet surface, thus reducing the chemical conversion treatment properties of the steel sheet. In the manufacturing of steel sheets, for example, they are often annealed at high temperatures after the cold-rolling process. Such high-temperature annealing can cause certain elements such as Sn contained in the steel to become uniformly concentrated on the steel sheet surface. For example, Sn-enriched areas, in a localized and relatively uneven concentration state formed after hot-rolling and pickling, become cathode sites during chemical conversion treatment. Therefore, rather than reducing the chemical conversion treatment properties, the Sn-enriched areas may actually improve them. However, subsequent high-temperature annealing homogenizes these relatively unevenly enriched areas. In addition, this high-temperature annealing causes diffusion of Sn from the inside of the steel sheet to the surface, promoting the homogenization of the Sn-enriched areas. It has been found that such uniform Sn enrichment inhibits the etching reaction on the steel sheet surface during the chemical conversion treatment, and can therefore cause poor chemical conversion treatment properties. Our recent investigation has revealed that when a steel sheet contains the three elements Ni, Cu, and Sn simultaneously, the concentration of Sn on the surface of the steel sheet during annealing, more specifically, the uniform concentration of Sn, can be particularly pronounced. In such cases, the chemical treatment properties of the steel sheet are greatly reduced, and consequently, the adhesion of the coating to the steel sheet is significantly reduced, which is problematic. While we do not intend to be bound by any particular theory, it is thought that when a steel sheet contains the three elements Ni, Cu, and Sn simultaneously, surface concentration of Sn is promoted due to co-segregation of these elements, etc.

[0013] Furthermore, there are generally two known methods for manufacturing steel plates: one involves obtaining molten iron in a blast furnace using iron ore, a natural resource, as the main raw material, and then producing molten steel through refining in a converter or the like; and the other involves producing molten steel in an electric arc furnace using scrap material, a recycled resource, as the main raw material. Blast furnace steel can also contain elements such as Ni, Cu, and Sn as additive elements, so when these elements are present, it is necessary to appropriately address the above-mentioned issues. On the other hand, electric arc furnace steel, as mentioned above, uses scrap material as the main raw material, and therefore contains a relatively large amount of scrap-derived elements such as Ni, Cu, and Sn (so-called trump elements), and thus the above-mentioned issues are particularly pronounced.

[0014] Therefore, the inventors investigated the elemental distribution on the surface of a steel sheet in order to suppress the concentration of Sn on the surface of the steel sheet, particularly during annealing, even when the steel sheet contains the three elements Ni, Cu, and Sn simultaneously, thereby improving the chemical treatment properties of the steel sheet and enhancing coating adhesion. As a result, the inventors first found that it is important to limit the amount of Sn on the surface of the steel sheet to a predetermined range. More specifically, they found that it is important to satisfy the aforementioned formula 1a, and that this can significantly improve the coating adhesion of the steel sheet. In addition, the inventors have found that increasing the amount of S in the surface portion of the steel plate is effective in satisfying formula 1a. More specifically, the inventors have found that increasing the amount of S in the surface portion of the steel plate is effective in satisfying the aforementioned formula 2a.

[0015] To explain in more detail, in the manufacture of steel sheets containing the three elements Ni, Cu, and Sn simultaneously, as described above, Sn may become concentrated on the surface of the steel sheet during the annealing process. Therefore, when the steel sheet is analyzed in the depth direction by XPS, it is expected that the amount of Sn on the surface of the steel sheet will be significantly higher than the amount of Sn in the bulk of the steel sheet. When such XPS analysis results are obtained, it is naturally recognized that the concentration of Sn on the surface of the steel sheet is significant, and therefore it is expected that the chemical treatment properties of the steel sheet and, consequently, the adhesion of the coating film will decrease. However, the inventors have found that, as will be explained in detail later in relation to the manufacturing method, by supplying a sulfur (S)-containing compound to the surface of the steel sheet before the annealing process, and furthermore, by carrying out the subsequent annealing process under appropriate conditions, S can be adsorbed onto the surface of the steel sheet, thereby suppressing the concentration of Sn on the surface of the steel sheet during the annealing process.

[0016] More specifically, the inventors adsorbed sulfur (S) onto the surface of a steel sheet by supplying an S-containing compound before the annealing process and then carrying out an appropriate annealing process. In the X-ray fluorescence analysis of the steel sheet finally obtained thereby, the surface S intensity I s1 and S strength I at the 1 / 4 plate thickness position s4 We found that it is possible to create a large amount of S on the surface of the steel sheet at a level that satisfies equation 2a, thereby suppressing the enrichment of Sn on the surface of the steel sheet during the annealing process. Although the reason is not entirely clear, due to the relatively high amount of S present on the steel sheet surface, the inventors were able to suppress the enrichment of Sn on the steel sheet surface during the annealing process, and more specifically, in the XPS analysis of the final steel sheet, the amount of Sn at a depth of 1 nm from the surface I sn1 and the amount of Sn at a depth of 200 nm from the surface I sn2 We found that if equation 1a is satisfied, it is possible to suppress the concentration of Sn on the surface of the steel sheet. Therefore, according to one embodiment of the steel sheet, it is possible to suppress or reduce the decrease in chemical conversion treatmentability caused by the concentration of Sn on the surface of the steel sheet.

[0017] In addition, subsequent studies by the inventors revealed that satisfying formula 2a allows S, which is relatively abundant on the surface of the steel sheet, to exhibit an effect of improving chemical conversion treatment properties. Therefore, according to the steel sheet according to one embodiment, the combination of the effect of improving chemical conversion treatment properties due to the suppression of Sn enrichment by satisfying formula 1a and the effect of improving chemical conversion treatment properties due to S itself by satisfying formula 2a makes it possible to significantly improve the chemical conversion treatment properties of the steel sheet, thereby significantly improving the adhesion of the coating film to the steel sheet.

[0018] One embodiment of the steel sheet includes not only electric furnace materials that inevitably contain Ni, Cu, and Sn as trump elements, but also blast furnace materials that contain Ni, Cu, and Sn as essential or optional additive elements. Furthermore, the steel sheet according to one embodiment makes it possible to achieve superior coating adhesion compared to conventional steel sheets that simultaneously contain all three elements: Ni, Cu, and Sn. Therefore, the steel sheet according to one embodiment is particularly useful for use in the automotive sector where excellent coating adhesion is required. The components of the steel sheet according to one embodiment will be described in more detail below.

[0019] [I sn1 / I sn2 ≤3.0] In one embodiment, in the analysis of a steel plate by X-ray photoelectron spectroscopy, the amount of Sn I at a depth of 1 nm from the surface of the steel plate is sn1 and the amount of Sn at a depth of 200 nm from the surface I sn2 The following equation 1a is satisfied. I sn1 / I sn2 ≤3.0 ···1a

[0020] I sn1 / I sn2 By keeping the value below 3.0, the concentration of Sn on the steel plate surface can be suppressed, thereby suppressing or reducing the decrease in chemical conversion treatment performance caused by the concentration of Sn on the steel plate surface, and ultimately improving the adhesion of the coating to the steel plate.

[0021] I sn1 / I sn2If the ratio exceeds 3.0, excessive concentration of Sn on the steel sheet surface may reduce the etching properties of Fe during chemical conversion treatment. In this case, the chemical conversion treatment properties of the steel sheet will decrease, resulting in reduced paint adhesion. From the viewpoint of further improving the paint adhesion of the steel sheet, I sn1 / I sn2 A smaller value is preferable. For example, I sn1 / I sn2 is 2.8 or less (i.e., I sn1 / I sn2 ≤2.8 (and so on), 2.5 or less, 2.2 or less, or 2.0 or less as shown in equation 1b below, and may also be 1.8 or less. The lower limit is not particularly limited, but for example, I sn1 / I sn2 It may be 1.0 or higher, or 1.1 or higher. I sn1 / I sn2 ≤2.0 ···1b

[0022] [I by X-ray photoelectron spectroscopy] sn1 / I sn2 [Measurement] I sn1 / I sn2 The measurement is performed by X-ray photoelectron spectroscopy as follows. First, a sample for measuring the intensity of Sn is prepared. Here, the sample is a steel plate cut from the target product, and the surface oil and dirt are removed using a solvent or the like. If the sample has a chemical conversion coating or paint film, these are removed by the method described below. The prepared sample is measured from the surface to a depth of 200 nm using a photoelectron spectrometer JPS-9200 manufactured by JEOL Ltd. Specifically, first, the inside of the sample holder of the instrument is evacuated. The pressure inside the holder during measurement is at most 3.0 × 10⁻⁶. -6 The pressure is Pa, and the maximum pressure inside the holder during sputtering is 1.0 × 10⁻⁶. -5The pressure is Pa. Before measuring the sample, the time required to sputter a 20nm thick SiO2 wafer is obtained. The time required to sputter 1nm and 200nm is determined by converting from the obtained time (for example, to sputter 1nm, sputtering is required for 1 / 20 of the time required to sputter 20nm, and to sputter 200nm, sputtering is required for 10 times the time required to sputter 20nm). The sputtering is 7.5 × 10⁻⁶. -2 The procedure is performed using Ar gas at Pa. Next, the sample is sputtered for the determined sputtering time, and the amount of Sn I at a depth of 1 nm from the surface of the sample is measured. sn1 and the amount of Sn I at a depth of 200 nm from the surface of the sample sn2 Measure I sn1 / I sn2 The amount of Sn is determined here by converting the intensity measured by XPS to at% using the "SPECSURF" software manufactured by JEOL Ltd. XPS can measure the amount of elements at the very surface (a few nm) of a material. In this specification, the amount of Sn measured by XPS on the newly exposed surface after removing the material from the surface of the steel plate to a depth of 1 nm or 200 nm by sputtering and then stopping the sputtering is referred to as the "amount of Sn at a depth of 1 nm from the surface" or the "amount of Sn at a depth of 200 nm from the surface". The specific measurement conditions for XPS are as follows. X-ray source: Mg source X-ray diameter: Φ1mm X-ray output: 12kV, 25mA Acceleration voltage: 3kV

[0023] [I s1 / I s4 ≥2.0] In one embodiment, in the analysis of a steel plate by X-ray fluorescence analysis, the surface S intensity I s1 and S strength I at the 1 / 4 plate thickness position s4 The following equation 2a is satisfied. I s1 / I s4 ≥2.0 ···2a

[0024] Is1 / I s4 By setting this to 2.0 or higher, it becomes possible to improve the chemical treatment properties of the steel sheet due to S itself, which is relatively abundant on the steel sheet surface, and to suppress the concentration of Sn on the steel sheet surface. Therefore, the combination of the effect of improving chemical treatment properties due to the suppression of Sn concentration by satisfying formula 1a and the effect of improving chemical treatment properties due to S itself by satisfying formula 2a makes it possible to significantly improve the chemical treatment properties of the steel sheet, thereby significantly improving the adhesion of the coating film on the steel sheet.

[0025] From the perspective of further improving the adhesion of the coating on steel plates, I s1 / I s4 A larger value is preferable. For example, I s1 / I s4 is 2.2 or greater (i.e., I s1 / I s4 ≥2.2 (the same applies below), 2.5 or higher, 2.8 or higher, or 3.0 or higher as per 2b below, and may also be 3.2 or higher. The upper limit is not particularly limited, but for example, I s1 / I s4 It may be 8.0 or less, 6.0 or less, 5.0 or less, or 4.5 or less. I s1 / I s4 ≥3.0 ···2b

[0026] [I by X-ray fluorescence analysis] s1 / I s4 [Measurement] I s1 / I s4 The measurement is performed by X-ray fluorescence analysis as follows. Specifically, first, if the steel plate has a chemical conversion coating or paint film, these are removed by the method described below. Next, the surface of the steel plate is irradiated with X-ray fluorescence to measure the intensity I, which is derived from the presence of element S. s1 To identify the element I. On the other hand, the surface of the steel plate at the 1 / 4 thickness position is exposed by grinding or the like, and the surface is similarly irradiated with fluorescent X-rays to determine the intensity I that originates from the presence of element S. s4 Identify the intensity I identified in this way. s1 and intensity I s4 Therefore, the intensity ratio Is1 / I s4 is determined. The measurement of S intensity by X-ray fluorescence shall be performed at 5 arbitrary positions on each of the steel sheet surface and the 1 / 4 thickness plane of the sheet, and based on the average value of the 5 positions, the above intensity ratio I s1 / I s4 is determined. The X-ray fluorescence measurement is performed using a Simultix14 apparatus manufactured by Rigaku Corporation, with an acceleration voltage of 30 kV, and is carried out until the maximum intensity in the obtained spectrum reaches 10000 counts. The maximum peak intensity at an energy of 2.3±0.3 keV is defined as the S intensity.

[0027] [Sn / (C+O+Fe+Mn+Si+Cu+Ni)≦0.010] In a preferred embodiment, in XPS analysis, the contents of Sn, C, O, Fe, Mn, Si, Cu and Ni at a depth of 1 nm from the steel sheet surface satisfy the following formula 3a, whereby the chemical conversion treatability of the steel sheet, and by extension the coating film adhesion, can be further improved. Sn / (C+O+Fe+Mn+Si+Cu+Ni)≦0.010 ···3a Here, Sn, C, O, Fe, Mn, Si, Cu and Ni are the contents of the respective elements in unit of at%.

[0028] Equation 3a can be understood as an equation that shows the amount of Sn on the surface of the steel sheet in relation to the main components in the steel. Therefore, the smaller the value of the left side of equation 3a, i.e., Sn / (C+O+Fe+Mn+Si+Cu+Ni), the smaller the absolute amount of Sn on the surface. Consequently, the smaller the left side of equation 3a, the less Sn concentration can be reduced on the surface of the steel sheet, and the more the chemical treatment properties of the steel sheet and, consequently, the adhesion of the coating can be improved. Regarding equation 3a, the Fe included in the denominator is a component of steel and is therefore almost constant at a value close to 100%, meaning the value of the denominator is almost constant. Therefore, the value of the left side of equation 3a mainly depends on the amount of Sn in the numerator. From the viewpoint of further improving the adhesion of the coating to the steel sheet, for example, Sn / (C+O+Fe+Mn+Si+Cu+Ni) may be 0.008 or less (i.e., Sn / (C+O+Fe+Mn+Si+Cu+Ni≦0.008, the same applies hereafter), 0.007 or less, 0.006 or less, or 0.005 or less). The lower limit is not particularly limited, but for example, Sn / (C+O+Fe+Mn+Si+Cu+Ni) may be 0.001 or more, or 0.002 or more.

[0029] [Measurement of Sn / (C+O+Fe+Mn+Si+Cu+Ni) by X-ray photoelectron spectroscopy] The measurement of Sn / (C+O+Fe+Mn+Si+Cu+Ni) involved measuring the amount of Sn, as well as the amounts of C, O, Fe, Mn, Si, Cu, and Ni at a depth of 1 nm from the surface of the sample, except that XPS was used for I2. sn1 / I sn2 The measurement is carried out under the same conditions as in the previous measurement. Based on the amounts of Sn, C, O, Fe, Mn, Si, Cu, and Ni at a depth of 1 nm from the surface of the sample obtained by XPS, the value of Sn / (C+O+Fe+Mn+Si+Cu+Ni) is determined.

[0030] [Chemical composition of steel sheets] In one embodiment, the steel sheet has a chemical composition containing, in mass%, Ni: 0.010 to 1.000%, Cu: 0.010 to 1.000%, and Sn: 0.003 to 1.000%. As described above, the present disclosure aims to provide a steel sheet containing Ni, Cu and Sn that can exhibit improved coating film adhesion, and in XPS analysis, the Sn content I at a position 1 nm deep from the steel sheet surface sn1 and the Sn content I at a position 200 nm deep from the surface sn2 limit the Sn content in the surface portion of the steel sheet so as to satisfy Formula 1a, and in analysis by X-ray fluorescence spectrometry, the S intensity I on the steel sheet surface s1 and the S intensity I at the 1 / 4 thickness position of the sheet s4 achieve the above object by increasing the S content in the surface portion of the steel sheet so as to satisfy Formula 2a. Therefore, the chemical composition of the steel sheet is not particularly limited except that it contains, in mass%, Ni: 0.010 to 1.000%, Cu: 0.010 to 1.000%, and Sn: 0.003 to 1.000%, so it is clear that elements other than Ni, Cu and Sn are not essential technical features for achieving the object of the present disclosure. The chemical composition of the steel sheet can contain, in addition to Ni, Cu and Sn, any alloying elements generally added in the technical field of the present disclosure in appropriate amounts. Hereinafter, the chemical composition of the steel sheet according to one embodiment will be described in detail, but these descriptions are merely intended as illustrations of preferred chemical compositions of steel sheets for application in automotive steel sheets and the like, and are not intended to limit the technology of the present disclosure to steel sheets having such specific chemical compositions.

[0031] In one embodiment, for example, the steel sheet contains, in mass%, C: 0.001 to 0.500%, Si: 0 to 3.00%, Mn: 0.10 to 3.00%, Al: 0.001 to 2.000%, Ni: 0.010 to 1.000%, Cu: 0.010 to 1.000%, Sn: 0.003 to 1.000%, P: 0.100% or less, S: 0.100% or less, N: 0.0150% or less, Ti: 0~0.150%, Nb: 0~0.150%, B: 0~0.0100%, Mo: 0~1.000%, Cr: 0~1.000%, V: 0~0.150%, W: 0~1.000%, Hf: 0~0.050%, Mg: 0~0.050%, Zr: 0~0.500%, Ca: 0~0.050%, REM: 0~0.010%, As: 0~0.100%, Ir: 0~1.000%, and Remainder: Fe and impurities It is preferable to have a chemical composition containing the following elements. Each element will be described in more detail below.

[0032] [C:0.001~0.500%] Carbon (C) is an element that increases strength inexpensively and is an important element for improving the strength of steel. To obtain this effect fully, it is preferable that the C content be 0.001% or more. The C content may also be 0.005% or more, 0.010% or more, 0.020% or more, 0.030% or more, 0.040% or more, 0.070% or more, 0.100% or more, 0.150% or more, or 0.200% or more. On the other hand, excessive C content may lead to a decrease in elongation. For this reason, it is preferable that the C content be 0.500% or less. The C content may also be 0.450% or less, 0.400% or less, 0.350% or less, 0.300% or less, or 0.250% or less.

[0033] [Si: 0~3.00%] Si is an effective element for increasing strength as a solid solution strengthening element. The Si content may be 0%, but to obtain such an effect, it is preferable that the Si content be 0.01% or more. The Si content may be 0.05% or more, 0.10% or more, 0.30% or more, 0.50% or more, 0.80% or more, or 1.00% or more. On the other hand, if the Si content is excessive, it may lead to a decrease in elongation along with an increase in steel strength. For this reason, it is preferable that the Si content be 3.00% or less. The Si content may be 2.50% or less, 2.00% or less, 1.50% or less, or 1.20% or less.

[0034] [Mn: 0.10~3.00%] Mn is an element that enhances the hardenability of steel and is effective in increasing its strength. To fully obtain these effects, it is preferable that the Mn content be 0.10% or more. The Mn content may also be 0.50% or more, 1.00% or more, 1.30% or more, 1.50% or more, or 1.80% or more. On the other hand, if the Mn content is excessive, it may lead to a decrease in elongation along with an increase in steel strength. For this reason, it is preferable that the Mn content be 3.00% or less. The Mn content may also be 2.80% or less, 2.50% or less, or 2.00% or less.

[0035] [Al:0.001~2.000%] Al acts as a deoxidizing agent for steel and is an element that has the effect of sounding down steel. To obtain this effect sufficiently, it is preferable that the Al content be 0.001% or more. The Al content may be 0.005% or more, 0.010% or more, 0.020% or more, or 0.030% or more. On the other hand, if the Al content is excessive, coarse Al oxide may be generated, which may reduce the elongation of the steel sheet. For this reason, it is preferable that the Al content be 2.000% or less. The Al content may be 1.500% or less, 1.000% or less, 0.500% or less, 0.100% or less, 0.050% or less, or 0.040% or less.

[0036] [Ni: 0.010~1.000%] [Cu: 0.010~1.000%] In one embodiment, the Ni and Cu content is 0.010% or more, respectively. Ni and Cu are elements that contribute to strength improvement through precipitation strengthening or solid solution strengthening. To fully obtain such effects, it is preferable that the content of these elements be 0.020% or more, and may be 0.030% or more, 0.040% or more, 0.050% or more, 0.080% or more, 0.100% or more, 0.150% or more, or 0.200% or more. On the other hand, if these elements are included in excessive amounts, the effect will saturate, and including them in the steel more than necessary will lead to an increase in manufacturing costs. Therefore, the Ni and Cu content is 1.000% or less, and may be 0.800% or less, 0.600% or less, 0.400% or less, or 0.300% or less, respectively.

[0037] [Sn: 0.003~1.000%] In one embodiment, the Sn content is 0.003% or more. Sn is an element effective in improving corrosion resistance. To fully obtain such an effect, the Sn content is preferably 0.004% or more, and may be 0.008% or more, 0.010% or more, 0.020% or more, 0.030% or more, 0.040% or more, 0.050% or more, 0.080% or more, or 0.100% or more. On the other hand, if the Sn content is excessive, it may promote the concentration of the steel sheet surface during annealing, which can lead to a decrease in chemical conversion treatment performance. Therefore, the Sn content should be 1.000% or less. The Sn content may also be 0.800% or less, 0.600% or less, 0.400% or less, 0.300% or less, 0.200% or less, 0.150% or less, or 0.120% or less.

[0038] [P:0.100% or less] P is an element that segregates at grain boundaries and promotes steel embrittlement. A lower P content is preferable, so the lower limit is 0%. However, excessive reduction of the P content can lead to a significant increase in cost. For this reason, the P content may be 0.0001% or more, or 0.001% or more, or 0.005% or more. On the other hand, excessive P content can lead to steel embrittlement due to grain boundary segregation, as described above. Therefore, it is preferable to have a P content of 0.100% or less. The P content may also be 0.050% or less, 0.030% or less, 0.020% or less, or 0.010% or less.

[0039] [S:0.100% or less] S is an element that generates nonmetallic inclusions such as MnS in steel, leading to a decrease in the ductility of steel parts. A lower S content is preferable, and therefore the lower limit is 0%. However, excessive reduction of the S content can lead to a significant increase in cost. For this reason, the S content may be 0.0001% or more, 0.0005% or more, 0.001% or more, or 0.002% or more. On the other hand, excessive S content can lead to cracking during cold forming, originating from nonmetallic inclusions. Therefore, it is preferable to have an S content of 0.100% or less. The S content may also be 0.050% or less, 0.020% or less, or 0.010% or less.

[0040] [N:0.0150% or less] N is an element that forms coarse nitrides in steel sheets, reducing their workability. A lower N content is preferable, and therefore the lower limit is 0%. However, excessive reduction of the N content can lead to a significant increase in manufacturing costs. For this reason, the N content may be 0.0001% or more, or 0.0005% or more, or 0.0010% or more. On the other hand, excessive N content can form coarse nitrides as described above, reducing the workability of the steel sheet. Therefore, it is preferable to have an N content of 0.0150% or less. The N content may also be 0.0100% or less, 0.0080% or less, 0.0060% or less, or 0.0050% or less.

[0041] The preferred basic chemical composition of the steel sheet is as described above. Furthermore, the steel sheet may optionally contain at least one of the following elements.

[0042] [Ti: 0~0.150%] [Nb: 0~0.150%] [V: 0~0.150%] Ti, Nb, and V have the effect of improving the strength of steel sheets by forming carbonitrides in the steel and strengthening through precipitation. The Ti, Nb, and V content may be 0%, but in order to obtain such an effect, the Ti, Nb, and V content is preferably 0.001% or more, and may be 0.002% or more, 0.005% or more, or 0.010% or more. On the other hand, if these elements are included in excess, the effect will saturate, and including them in the steel more than necessary will lead to an increase in manufacturing costs. Therefore, the Ti, Nb, and V content is preferably 0.150% or less, and may be 0.120% or less, 0.100% or less, 0.080% or less, 0.050% or less, 0.020% or less, or 0.015% or less.

[0043] [B: 0~0.0100%] B improves low-temperature toughness by segregating at grain boundaries and increasing grain boundary strength. The B content may be 0%, but to obtain this effect, it is preferable that the B content be 0.0001% or more. The B content may also be 0.0002% or more, 0.0005% or more, or 0.0010% or more. On the other hand, if the B content is excessive, the effect will saturate, which may lead to an increase in manufacturing costs. Therefore, it is preferable that the B content be 0.0100% or less. The B content may also be 0.0050% or less, 0.0030% or less, 0.0020% or less, or 0.0015% or less.

[0044] [Mo: 0~1.000%] [Cr: 0~1.000%] [W: 0~1.000%] Mo, Cr, and W are elements that enhance the hardenability of steel and contribute to improving its strength. While the content of Mo, Cr, and W may be 0%, to obtain such effects, it is preferable that the content of Mo, Cr, and W be 0.001% or more, and may be 0.010% or more, 0.020% or more, or 0.030% or more. On the other hand, if these elements are included in excess, the effect will saturate, and including them in the steel more than necessary will lead to an increase in manufacturing costs. Therefore, it is preferable that the content of Mo, Cr, and W be 1.000% or less, and may be 0.800% or less, 0.500% or less, 0.100% or less, 0.050% or less, or 0.040% or less.

[0045] [Hf: 0~0.050%] [Mg: 0~0.050%] [Zr:0~0.500%] [Ca: 0~0.050%] [REM: 0~0.010%] Hf, Mg, Zr, Ca, and REM are elements that can control the morphology of nonmetallic inclusions. The content of Hf, Mg, Zr, Ca, and REM may be 0%, but to obtain such an effect, the content of each of these elements is preferably 0.0001% or more, and may be 0.0005% or more, or 0.001% or more. On the other hand, if these elements are included in excess, the effect will saturate, and including them in the steel sheet more than necessary will lead to an increase in manufacturing costs. Therefore, the content of Hf, Mg, and Ca is preferably 0.050% or less, and may be 0.010% or less, 0.005% or less, or 0.003% or less, respectively. Similarly, the Zr content is preferably 0.500% or less, and may be 0.100% or less, 0.010% or less, 0.005% or less, or 0.003% or less. Similarly, the REM content is preferably 0.010% or less, and may be 0.005% or less, or 0.003% or less. REM stands for Rare Earth Metal, and refers to a total of 17 elements: scandium (Sc) and yttrium (Y), plus 15 other elements from lanthanum (La) to lutetium (Lu). The REM content is the sum of the content of these 17 elements.

[0046] [As: 0~0.100%] As is an element effective in improving corrosion resistance. While the As content may be 0%, it is preferable that the As content be 0.001% or more to obtain such an effect. The As content may also be 0.002% or more, or 0.003% or more. On the other hand, if the As content is excessive, the effect will saturate, and including more As than necessary in the steel sheet will lead to an increase in manufacturing costs. Therefore, it is preferable that the As content be 0.100% or less. The As content may also be 0.010% or less, 0.008% or less, or 0.005% or less.

[0047] [Ir: 0~1.000%] Ir is an element that segregates at prior austenite grain boundaries, increasing their strength. While the Ir content may be 0%, it is preferable that the Ir content be 0.001% or higher to obtain this effect. The Ir content may also be 0.003% or higher, 0.005% or higher, or 0.010% or higher. On the other hand, excessive Ir content leads to saturation of the effect, and including more Ir than necessary in the steel increases manufacturing costs. Therefore, it is preferable that the Ir content be 1.000% or lower. The Ir content may also be 0.500% or lower, 0.100% or lower, 0.030% or lower, or 0.015% or lower.

[0048] In the steel sheet, the remainder other than the elements mentioned above consists of Fe and impurities. Impurities in the steel sheet include components that are mixed in due to various factors in the manufacturing process, such as raw materials like ore and scrap, during the industrial production of the steel sheet, as well as components that are included to the extent that they do not affect the effects of the present invention.

[0049] The chemical composition of steel sheets can be measured using general analytical methods. For example, the chemical composition of steel sheets can be measured using ICP-AES (Inductively Coupled Plasma-Atomic Emission Spectrometry) in accordance with JIS G 1201:2014. Specifically, a 35mm square test specimen (for example, a 35mm square specimen with a sample thickness of 3 / 4 of the base steel sheet thickness) is obtained, machined so that the analysis surface is located 1 / 4 of the thickness of the base steel sheet from the surface of the base steel sheet and parallel to the surface of the base steel sheet. The chemical composition can then be determined by measuring it using a Shimadzu ICPS-8100 or similar (measuring device) under conditions based on a pre-established calibration curve. C and S, which cannot be measured by ICP-AES, can be measured using the combustion-infrared absorption method, and N can be measured using the inert gas fusion-thermal conductivity method. If analysis values ​​for molten steel, slabs, or other steel sheets manufactured from the same molten steel are available, the analysis of test pieces taken from the steel sheet may be omitted, and those analysis values ​​may be considered as the chemical composition of the steel sheet.

[0050] [Thickness of steel plate] The thickness of the steel plate is not particularly limited, but generally it is between 0.2 and 8.0 mm. For example, the thickness may be 0.3 mm or more, 0.6 mm or more, 1.0 mm or more, 1.6 mm or more, or 2.0 mm or more. Similarly, the thickness of the steel plate may be, for example, 7.0 mm or less, 6.0 mm or less, 5.0 mm or less, or 4.0 mm or less.

[0051] [Mechanical properties] The steel plate according to one embodiment is not particularly limited, but may have a Vickers hardness of, for example, 90 Hv or more. The Vickers hardness may be 150 Hv or more, 190 Hv or more, 200 Hv or more, 250 Hv or more, 300 Hv or more, 350 Hv or more, 400 Hv or more, or 450 Hv or more. The upper limit is not particularly limited, but for example, the Vickers hardness may be 650 Hv or less, 600 Hv or less, 550 Hv or less, or 500 Hv or less.

[0052] [Measurement of Vickers hardness] Vickers hardness is determined in accordance with JIS Z 2244-1:2024 as follows: First, a test piece is cut from any position except the edge of the steel plate so that a cross section perpendicular to the surface (thickness cross section) can be observed. The thickness cross section of the test piece is polished using #600 to #1500 silicon carbide sandpaper, and then polished to a mirror finish using a liquid in which diamond powder with a particle size of 1 to 6 μm is dispersed in a diluent such as alcohol or pure water, and this thickness cross section is used as the measurement surface. Next, the Vickers hardness is measured using a micro Vickers hardness tester with a test force of 9.807 N at intervals of at least three times the average value of the diagonal length of the indentation. Specifically, a total of 20 points are randomly measured at 1 / 4 positions of the steel plate thickness, and the arithmetic mean of these measurements is determined as the Vickers hardness of the steel plate.

[0053] As described above, the steel sheet according to one embodiment can achieve superior coating adhesion compared to conventional steel sheets containing the three elements Ni, Cu, and Sn simultaneously. Therefore, the steel sheet according to one embodiment is useful for use in parts in technical fields where superior coating adhesion is required, and is particularly useful for use in automotive parts. In a preferred embodiment, an automotive part including the steel sheet according to one embodiment is provided. Examples of automotive parts include frame parts, bumpers, other structural and reinforcing parts that require strength, and exterior parts such as roofs, hoods, fenders, and doors that require high aesthetic appeal. These parts only need to include the steel sheet according to one embodiment in at least a portion of them, and therefore at least a portion of these parts will satisfy the characteristics of the steel sheet described above. In forming processes such as press forming, the characteristics of the steel sheet do not particularly change before and after forming in parts of the steel sheet that do not directly contact the mold or that are processed to a relatively low degree even if they do directly contact the mold.

[0054] <Method of manufacturing steel plates> Next, a preferred method for manufacturing a steel sheet according to one embodiment will be described. The following description is intended to illustrate a characteristic method for manufacturing a steel sheet according to one embodiment, and is not intended to limit the steel sheet to those manufactured by the manufacturing method described below.

[0055] A steel sheet according to one embodiment can be manufactured by, for example, a casting step of casting molten steel with an adjusted chemical composition to form a slab; a hot rolling step of hot rolling the slab to obtain a hot-rolled steel sheet; a winding step of winding the hot-rolled steel sheet and then pickling it; a brush grinding step of brush grinding the obtained hot-rolled steel sheet; a cold rolling step of cold rolling the brush-ground hot-rolled steel sheet to obtain a cold-rolled steel sheet; a coating step of applying an S-containing compound to the obtained cold-rolled steel sheet; and an annealing step of annealing the cold-rolled steel sheet to which the S-containing compound has been applied. Each step will be described in detail below.

[0056] [Casting Process] The conditions for the casting process are not particularly limited. For example, after melting in a blast furnace or electric furnace, various secondary smelting processes may be carried out, followed by the production of slabs by conventional continuous casting or by methods such as rolling out the ingots after ingot formation.

[0057] [Hot rolling process] Hot-rolled steel sheets can be obtained by hot-rolling a slab. The hot-rolling process is carried out by hot-rolling the cast slab either directly or after it has been cooled and then reheated. When reheating is performed, the heating temperature of the slab may be, for example, 1100 to 1250°C. In the hot-rolling process, rough rolling and finish rolling are usually performed. The temperature and reduction ratio of each rolling step can be appropriately determined according to the desired metal structure and sheet thickness. For example, the finishing temperature of the finish rolling may be 900 to 1050°C, and the reduction ratio of the finish rolling may be 10 to 50%.

[0058] [Winding process] The hot-rolled steel sheet obtained in the hot-rolling process is wound in the next winding process and then pickled. The winding temperature is not particularly limited and can be appropriately determined according to the desired metal structure, etc. For example, the winding temperature may be 500°C or lower. The pickling is not particularly limited and should be carried out using a commonly used pickling solution under conditions suitable for removing the oxide scale formed on the surface of the hot-rolled steel sheet. Pickling may be carried out once or in multiple steps to ensure the removal of the oxide scale.

[0059] [Brush grinding process] The obtained hot-rolled steel sheet is then subjected to the next brush grinding process, with a grinding amount of 3.0 g / m². 2 Brush grinding is performed under the above conditions. By performing brush grinding under these conditions, Sn-enriched areas on the surface of the hot-rolled steel sheet can be sufficiently or completely removed. As a result, the enrichment of Sn on the surface of the steel sheet during the subsequent annealing process can be significantly suppressed or reduced. Therefore, it is possible to improve the chemical conversion treatment properties and, consequently, the coating adhesion of the final steel sheet.

[0060] Either no brush grinding is performed, or if brush grinding is performed, the amount of material removed is 3.0 g / m². 2 If the amount is less than this, it becomes impossible to adequately remove the Sn-enriched areas on the surface of the hot-rolled steel sheet. As a result, even if the coating process of the sulfur-containing compound, which will be explained in detail later, is properly carried out, the Sn enrichment will be promoted during the subsequent annealing process, starting from the Sn-enriched areas remaining after the winding process. For example, the locally present Sn-enriched areas may become uniformly present across the entire surface of the steel sheet. In this case, the amount of Sn at a depth of 1 nm from the surface can be determined by XPS analysis of the final steel sheet. sn1 and the amount of Sn at a depth of 200 nm from the surface I sn2 This means that the aforementioned equation 1a can no longer be satisfied. As a result, the chemical treatment properties of the steel sheet and, consequently, the adhesion of the coating film will decrease. For example, if the amount of thickness reduction due to pickling in the winding process is 3.0 g / m 2 Even if the above conditions are met, either do not perform brush grinding or the amount of grinding by brush grinding is 3.0 g / m 2If the concentration is less than the limit, the remaining Sn-enriched areas after the winding process will serve as a starting point for further Sn enrichment during the subsequent annealing process. Consequently, the chemical conversion treatment properties of the steel sheet and, consequently, the adhesion of the coating will decrease.

[0061] From the viewpoint of thoroughly removing the Sn-enriched areas and improving the chemical conversion treatment properties and coating adhesion of the final steel sheet, a larger amount of abrasive material removed by brush grinding is preferable, for example, 6.0 g / m². 2 The above is preferable. The upper limit of the grinding amount is not particularly limited, but for example, 15.0 g / m 2 The following or 10.0 g / m 2 The following may also apply. The amount of grinding by the grinding brush can be adjusted by any suitable method known to those skilled in the art. Although not particularly limited, the amount of grinding by the grinding brush can be adjusted by appropriately selecting, for example, the type of grinding brush (e.g., Hotani H115), the number of grinding brushes, the rotation speed, the amount of brush reduction, and the coating liquid used. The brush grinding process may be performed before the annealing process and the coating process, or after the cold rolling process. However, if performed after the cold rolling process, the surface quality of the cold-rolled steel sheet may be impaired, so it is preferable to perform the brush grinding process before the cold rolling process.

[0062] [Cold rolling process] After brush grinding a hot-rolled steel sheet, a cold-rolled steel sheet can be obtained by cold-rolling the hot-rolled steel sheet. The reduction ratio during cold rolling can be appropriately determined according to the desired metal structure and sheet thickness, and may be, for example, 20 to 80%. After the cold-rolling process, the sheet may be cooled to room temperature by air cooling, for example.

[0063] [Coating process] In the next coating step, a sulfur-containing compound, more specifically an aqueous solution containing the sulfur-containing compound, is applied to the surface of the cold-rolled steel sheet. This allows sufficient adsorption of the sulfur component from the sulfur-containing compound onto the surface of the cold-rolled steel sheet, thereby suppressing the concentration of sulfur (Sn) on the steel sheet surface during the subsequent annealing process. Therefore, in the analysis of the final steel sheet by X-ray fluorescence analysis, the surface sulfur intensity I s1and S strength I at the 1 / 4 plate thickness position s4 The above equation 2a is satisfied, and furthermore, the amount of Sn I at a depth of 1 nm from the surface in the XPS analysis of the final steel sheet is also satisfied. sn1 and the amount of Sn at a depth of 200 nm from the surface I sn2 This ensures that the above-mentioned formula 1a is satisfied. As a result, it becomes possible to improve the chemical treatment properties of the steel sheet and, consequently, the adhesion of the coating film.

[0064] If the sulfur-containing compound is not applied before the annealing process, sulfur will not be adsorbed onto the steel sheet surface, making it impossible to suppress the concentration of sulfur (Sn) on the steel sheet surface during the subsequent annealing process. In this case, it will not be possible to have a large amount of sulfur on the surface of the steel sheet at a level that satisfies equation 2a, and related to this, the amount of sulfur (I) at a depth of 1 nm from the steel sheet surface. sn1 and the amount of Sn at a depth of 200 nm from the surface I sn2 This makes it impossible to suppress the concentration of Sn on the steel sheet surface at a level that satisfies equation 1a. As a result, the chemical treatment properties of the steel sheet and, consequently, the adhesion of the coating film will decrease.

[0065] The method for applying the sulfur-containing compound is not particularly limited and may be any suitable method known to those skilled in the art. For example, the application method may be spraying or immersion. The sulfur-containing compound is not particularly limited, but can be used, for example, as an aqueous solution containing the sulfur-containing compound at a concentration of 10 to 1500 ppm. The sulfur-containing compound is not particularly limited as long as it contains sulfur, but is preferably an sulfur-containing organic compound such as thioglycolic acid, thiosulfuric acid, thiocyanic acid, thiocarboxylic acid, thiourea, sodium thiosulfate, and / or ammonium thiosulfate, dimethyl sulfide, 2,2'-dithioethanol, 1,1'-thiocarbonyldiimidazole, disulfide, thiocarbonyl, thiol, or sodium sulfate. Those skilled in the art can determine the preferred concentration of the sulfur-containing compound in the aqueous solution and the preferred amount of the aqueous solution applied without excessive trial and error, for example, by examining the performance of steel sheets manufactured by changing these parameters to multiple values.

[0066] [Annealing process] Next, the cold-rolled steel sheet coated with an S-containing compound, and thus onto which S is adsorbed, is annealed. The annealing process involves heating the cold-rolled steel sheet to an annealing temperature of 700-950°C in an atmosphere with a dew point of -40°C or lower and a hydrogen concentration of 5% by volume or higher (nitrogen in addition to hydrogen), and holding it for 10 seconds or more. By carrying out the annealing process under these conditions, it is possible to suppress the desorption of S adsorbed on the surface of the cold-rolled steel sheet during the annealing process. Therefore, in the analysis of the finally obtained steel sheet by X-ray fluorescence analysis, the surface S intensity I s1 Furthermore, the S strength at the 1 / 4 thickness position satisfies equation 2a, and similarly, the amount of Sn I at a depth of 1 nm from the surface in the XPS analysis of the final steel plate. sn1 and the amount of Sn at a depth of 200 nm from the surface I sn2 This ensures that the formula satisfies equation 1a. As a result, it becomes possible to improve the chemical treatment properties of steel plates and, consequently, the adhesion of the coating film.

[0067] If the dew point is above -40°C, the hydrogen concentration is less than 5% by volume, and / or the annealing temperature is above 950°C, sulfur adsorbed on the surface of the cold-rolled steel sheet will combine with oxygen and other elements and detach from the steel sheet surface, promoting the concentration of sulfur (Sn) on the steel sheet surface during the annealing process. In this case, it will not be possible to have a large amount of sulfur on the surface of the steel sheet at a level that satisfies equation 2a in the final steel sheet, and related to this, the amount of Sn at a depth of 1 nm from the steel sheet surface I sn1 and the amount of Sn at a depth of 200 nm from the surface I sn2 If the level satisfies Equation 1a, it becomes impossible to suppress the concentration of Sn on the steel sheet surface. As a result, the chemical treatment properties of the steel sheet and, consequently, the adhesion of the coating film will decrease. From the viewpoint of further improving the chemical treatment properties of the steel sheet and, consequently, the adhesion of the coating film, by suppressing the desorption of S from the steel sheet surface and the surface concentration of Sn, it is preferable to carry out the annealing process under conditions of a lower dew point and a higher hydrogen concentration. For example, by carrying out the annealing process under conditions of a dew point of -50°C or lower and / or a hydrogen concentration of 8 volume% or higher, the desorption of S from the steel sheet surface and the surface concentration of Sn can be suppressed more significantly. In this case, for example, the left side of Equation 2a, i.e., I s1 / I s4 At a level where is 3.0 or higher, more S can be present on the surface portion of the steel plate, and / or the left side of equation 1a, i.e., I sn1 / I sn2 At a level where the concentration of Sn on the steel sheet surface is 2.0 or less, it becomes possible to more significantly suppress this concentration. As a result, the chemical treatment properties of the steel sheet and, consequently, the adhesion of the coating film can be significantly improved.

[0068] In particular, when the annealing process is carried out under conditions where the dew point is -50°C or lower and the hydrogen concentration is 8% by volume or higher, s1 / I s4 S is present on the surface portion of the steel plate at a level of 3.0 or higher, and I sn1 / I sn2In addition to suppressing Sn enrichment on the steel sheet surface at a level where the ratio is 2.0 or less, it is also possible to suppress Sn enrichment on the steel sheet surface at a level where the amounts of Sn, C, O, Fe, Mn, Si, Cu, and Ni at a depth of 1 nm from the steel sheet surface satisfy Sn / (C+O+Fe+Mn+Si+Cu+Ni)≦0.007. Therefore, in this case, it is possible to further improve the chemical conversion treatment properties of the steel sheet and, consequently, the adhesion of the coating film.

[0069] The lower limit of the dew point in the annealing process is not particularly limited, but for example, the dew point may be -80°C or higher or -60°C or higher. Similarly, the upper limit of the hydrogen concentration in the annealing process is not particularly limited, but for example, the hydrogen concentration may be 12% by volume or less or 10% by volume or less (nitrogen in addition to hydrogen). Furthermore, the holding time at the annealing temperature of 700 to 950°C in the annealing process is preferably 180 seconds or less from the viewpoint of productivity. In this manufacturing method, pickling is not performed after the annealing process.

[0070] According to this manufacturing method, in steel sheets where coating adhesion is difficult to improve due to the simultaneous presence of three elements, Ni, Cu, and Sn, in particular, first, in the brush grinding process, the Sn-enriched areas on the surface of the hot-rolled steel sheet are sufficiently removed by appropriately brush grinding the hot-rolled steel sheet. Next, an aqueous solution containing an S-containing compound is applied to the surface of the cold-rolled steel sheet, thereby allowing sufficient adsorption of the S component from the S-containing compound onto the surface of the cold-rolled steel sheet. Subsequently, by appropriately controlling the dew point and hydrogen concentration in the annealing process, it is possible to suppress the desorption of adsorbed S and the surface enrichment of Sn. In relation to the desorption of S from the steel sheet surface and the suppression of surface enrichment of Sn, the surface S intensity I was determined by X-ray fluorescence analysis. s1 and S strength I at the 1 / 4 plate thickness position s4 The equation satisfies equation 2a, and furthermore, the amount of Sn I at a depth of 1 nm from the surface in the analysis by XPS is sn1 and the amount of Sn at a depth of 200 nm from the surface I sn2This method allows for the production of steel sheets that satisfy formula 1a. As a result, the combination of the improved chemical treatment properties due to the suppression of Sn enrichment by satisfying formula 1a and the improved chemical treatment properties due to S itself by satisfying formula 2a significantly improves the chemical treatment properties of the steel sheets, thereby significantly improving the adhesion of the coatings to the steel sheets. Therefore, steel sheets produced by this manufacturing method can achieve superior coating adhesion compared to conventional steel sheets that simultaneously contain the three elements Ni, Cu, and Sn. Consequently, they can contribute to industrial development by extending the lifespan of steel sheets used in automobiles and building materials.

[0071] A steel sheet according to one embodiment can be used as one of the various automotive parts described above, for example, after a chemical conversion coating or paint film is arbitrarily formed on its surface. Whether or not an automotive part having a paint film or chemical conversion coating includes a steel sheet according to one embodiment can be determined by removing the paint film or chemical conversion coating from a sample taken from the automotive part. The sample collection location, paint film removal process, and chemical conversion coating removal process in this case are as follows.

[0072] [Sample collection location] When collecting samples from automotive parts, avoid the following locations (i) to (iv). (i) Within 20 mm of the toe of a spot weld, and within 20 mm of the toe of the bead of an arc / laser weld. (ii) Machining area with a radius of curvature of less than 15 mm, and areas within 5 mm of said machining area (iii) Ends within 5 mm from the cut end face of the part (iv) Areas within 5 mm of the area where red rust is visible to the naked eye

[0073] [Paint film removal process] For a sample cut from the automobile body, the paint film is removed under the following conditions to expose the steel plate. A paint remover (Neoriver #160, manufactured by Sansai Chemical Co., Ltd.) is applied to the surface at room temperature and left to stand for about 5 minutes. Then, the paint film is removed by rubbing with a hard sponge or the like (e.g., Kanefeel, manufactured by AION Co., Ltd.). After that, it is washed with water and dried. At this time, the remaining state of the paint film is confirmed by SEM-EPMA measurement of the sample surface (100 μm square, 5 fields of view) after washing with water and drying. In the elemental distribution image obtained by EPMA, regions with a C concentration of 10 mass% or more are identified, and if the area ratio of these regions is 5% or more, it is judged that the paint film has not been removed sufficiently. To measure the area ratio of regions with a C concentration of 10 mass% or more, first, an elemental distribution image of C is obtained in EPMA with the C concentration range set to 10-30%. The specific measurement conditions for EPMA are as follows. Equipment: JEOL Ltd. JXA-8230 Electron Probe Microanalyzer Acceleration voltage: 15kV Irradiation current: 0.05μA Surface analysis:WDS Analysis interval: 300 μm or longer Area ratio: Average value of 5 fields of view Next, the area fraction is measured by image processing of the obtained elemental distribution image. The image analysis software "ImageJ" is used for image processing. After loading the elemental distribution image of C into ImageJ, the image is binarized using "Make Binary" in "Process" > "Binary" so that areas with a C concentration of 10 mass% or more are displayed in black and areas with a C concentration of less than 10 mass% are displayed in white. After binarization, the value of "Area fraction" in "Results" is read using "Measure" in "Analyze" and this value is determined as the area fraction of the areas with a C concentration of 10 mass% or more. If the paint film is not sufficiently removed, the removal of the paint film is repeated until the area fraction of the areas with a C concentration of 10 mass% or more is less than 5%.

[0074] [Removal of chemical conversion coating] For samples cut from the automobile body and with the paint film removed, if the chemical conversion coating is, for example, a zinc phosphate coating, the chemical conversion coating is removed in accordance with JIS K 3151:1996. Specifically, the chemical conversion coating is removed by immersion in a 5% chromic acid aqueous solution heated to 75°C for 15 minutes. After that, it is washed with water and dried. At this time, the remaining state of the chemical conversion crystals is confirmed by SEM-EPMA measurement of the sample surface (100 μm square, 5 fields of view) after washing with water and drying. In the elemental distribution image obtained by EPMA, regions where the P concentration is 5% by mass or more are identified, and if the area ratio of the region is 5% or more, it is judged that the chemical conversion coating has not been removed sufficiently. To measure the area ratio of regions where the P concentration is 5% by mass or more, first, an elemental distribution image of P is obtained in EPMA with the P concentration range set to 5-10%. Then, the area ratio is measured by image processing of the obtained elemental distribution image. Image processing is performed using the image analysis software "ImageJ". After loading the elemental distribution image of P into ImageJ, the image is binarized using "Make Binary" in "Process" > "Binary" so that areas with a P concentration of 5 mass% or more are displayed in black and areas with a P concentration of less than 5 mass% are displayed in white. After binarization, the value of "Area fraction" in "Results" is read using "Measure" in "Analyze" and this value is determined as the area percentage of areas with a P concentration of 5 mass% or more. If the chemical conversion coating is not sufficiently removed, the removal of the chemical conversion coating is repeated until the area percentage of areas with a P concentration of 5 mass% or more is less than 5%.

[0075] The present invention will be described in more detail below with reference to examples, but these examples are merely examples of the present invention, and the present invention is not limited in any way to these examples. Needless to say, the present invention can be modified as desired without departing from the spirit of the invention. [Examples]

[0076] In the following embodiments, a steel sheet according to one embodiment was manufactured under various conditions, and the properties of the manufactured steel sheet were investigated.

[0077] First, molten steel was cast using a continuous casting method to form a slab having the chemical composition (molten steel analysis values) shown in Table 1. After the slab was cooled, it was reheated to 1200°C and hot-rolled. Hot rolling was carried out by rough rolling and finish rolling, with the finish rolling ending at a temperature of 900-1050°C and a reduction ratio of 30%. Next, the hot-rolled steel sheet was wound at a winding temperature of 500°C or less, pickled, and then brush-grinding (H115 manufactured by Hotani Co., Ltd.) was performed with the brush grinding amount shown in Table 2. Next, the hot-rolled steel sheet was cold-rolled with a reduction ratio of 50% to obtain a cold-rolled steel sheet with a thickness of 1.6 mm. Next, an aqueous solution containing 1000 ppm of thioglycolic acid, dimethyl sulfide, or sodium sulfate as a sulfur-containing compound was applied to the surface of the obtained cold-rolled steel sheet. Then, an annealing process was carried out in a furnace with an oxygen concentration of 20 ppm or less, in an atmosphere with the dew point and hydrogen concentration (nitrogen if not hydrogen) shown in Table 2, at a temperature of 800°C and held for 100 seconds to obtain a steel sheet containing Ni, Cu, and Sn.

[0078] [Table 1]

[0079] [Table 2]

[0080] The properties of the obtained steel sheets were measured and evaluated by the following methods. Measurements of features and properties not specifically described in the examples were carried out as described herein.

[0081] [Evaluation of coating adhesion] The adhesion of the coating film was evaluated as follows. First, a 50mm x 50mm sample of the steel plate manufactured above was subjected to a chemical conversion treatment of zinc phosphate or zirconium under the following conditions. (Zinc phosphate treatment) Degreasing: Immerse in a degreasing agent (Fine Cleaner E2001) at 40°C for 2 minutes, then rinse with water. Surface preparation: Immerse in a surface preparation agent (Preparen Z) at room temperature for 30 seconds. Chemical treatment: Immerse in zinc phosphate treatment agent (Palbond L3020) at 40°C for 2 minutes, then rinse with water and dry. (Zirconium treatment) Degreasing: Immerse in a degreasing agent (Fine Cleaner E2001) at 40°C for 2 minutes, then rinse with water. Chemical treatment: Immerse in zirconium treatment agent (PLC-2010) at 45°C for 3 minutes, then rinse with water and dry.

[0082] A sample of chemically treated steel plate was coated with electrodeposition paint (Powerfloat 1200: manufactured by Nippon Paint Industrial Coatings Co., Ltd.) at an electrodeposition temperature of 30°C and a film thickness of 18 μm, followed by a baking treatment at 170°C for 30 minutes. Next, a saltwater immersion test (SDT) was performed on the electrodeposited sample. Specifically, the electrodeposited sample was immersed in a 5% NaCl aqueous solution at 60°C for 1500 hours. After the SDT test, the sample was removed and dried, and then a tape peel test was performed on one side of the sample. The peeled tape was scanned, and the area percentage of the paint film that had peeled off was calculated by binarization using the image analysis software "ImageJ". The paint film adhesion was evaluated as follows. AAA: Peeling area ratio less than 10% AA: Peeling area ratio less than 10-15% A: Peeling area ratio less than 15-20% B: Peeling area ratio of 20% or more

[0083] Steel sheets containing Ni, Cu, and Sn were evaluated as having improved coating adhesion when the coating adhesion rating was AAA, AA, or A. The results are shown in Table 2. In Table 2, "P" for the type of chemical conversion coating means zinc phosphate coating, and similarly, "Zr" means zirconium-based coating, specifically a coating containing zirconium oxide. Also in Table 2, the amount of wall thickness reduction (g / m²) after pickling is shown. 2 The "-" in the brackets indicates that the amount of material loss due to pickling was not measured.

[0084] Referring to Table 2, it is thought that in Comparative Examples 24 and 26, brush grinding was not performed, and therefore the Sn-enriched areas on the surface of the hot-rolled steel sheets could not be sufficiently removed. Therefore, it is thought that the Sn-enriched areas remaining after the winding process served as a starting point for the subsequent annealing process, which accelerated the Sn enrichment. As a result, in the XPS analysis of the final steel sheets, the amount of Sn at a depth of 1 nm from the surface was sn1 and the amount of Sn at a depth of 200 nm from the surface I sn2 However, the concentration of Sn on the steel sheet surface could no longer be suppressed at a level that satisfies the aforementioned formula 1a, and as chemical conversion treatment performance decreased, coating adhesion decreased. In particular, in Comparative Example 26, prolonged immersion in the pickling solution during the winding process resulted in a thinning of 3.0 g / m² due to pickling. 2 Despite the above, the lack of brush grinding resulted in a decrease in chemical conversion treatment properties and reduced paint adhesion, as described above. The amount of wall thickness reduced by pickling was 3.0 g / m². 2 Even with the above explanation, the reason why corrosion resistance cannot be improved remains unclear, but it is possible that Sn and other elements that were dissolved in the pickling solution remain on the surface of the hot-rolled steel sheet.

[0085] In Comparative Example 25, although brush grinding was performed, the amount of brush grinding was insufficient, and similarly, the Sn-enriched areas on the surface of the hot-rolled steel sheet could not be sufficiently removed. It is thought that the Sn-enriched areas remaining after the winding process served as the starting point for the subsequent annealing process, which accelerated the Sn enrichment. As a result, in the XPS analysis of the final steel sheet, the amount of Sn at a depth of 1 nm from the surface was sn1 and the amount of Sn at a depth of 200 nm from the surface I sn2 The concentration of Sn on the steel plate surface could no longer be suppressed at a level that satisfies Equation 1a, and as a result of the decrease in chemical conversion treatment properties, the adhesion of the coating film decreased.

[0086] In Comparative Example 27, because the sulfur-containing compound was not applied before the annealing process, sulfur was not adsorbed onto the steel sheet surface, and it is believed that the concentration of sulfur on the steel sheet surface during the subsequent annealing process could not be suppressed. As a result, in the final steel sheet, it was not possible to create a sufficient amount of sulfur on the surface of the steel sheet to satisfy the aforementioned formula 2a, and the concentration of sulfur on the steel sheet surface could not be suppressed to satisfy the aforementioned formula 1a. Consequently, the adhesion of the coating film decreased along with the decrease in chemical conversion treatmentability.

[0087] In Comparative Example 28, although the sulfur-containing compound was applied after the annealing process, it was not applied before the annealing process. As a result, sulfur was not adsorbed onto the steel sheet surface before the annealing process, and it is believed that the concentration of Sn on the steel sheet surface during the subsequent annealing process could not be suppressed. Therefore, in the final steel sheet obtained, the amount of Sn at a depth of 1 nm from the steel sheet surface was sn1 and the amount of Sn at a depth of 200 nm from the surface I sn2 The concentration of Sn on the steel plate surface could not be suppressed at a level that satisfied equation 1a. As a result, the adhesion of the coating film decreased along with the decrease in chemical conversion treatment properties.

[0088] In Comparative Example 29, the dew point was high during the annealing process, which is thought to have caused sulfur adsorbed on the surface of the cold-rolled steel sheet to detach during the annealing process, thus promoting the concentration of Sn on the steel sheet surface. As a result, it was not possible to achieve a level of high S content on the surface of the steel sheet that satisfies Equation 2a in the final steel sheet, and related to this, the amount of Sn I at a depth of 1 nm from the steel sheet surface sn1 and the amount of Sn at a depth of 200 nm from the surface I sn2However, the concentration of Sn on the steel sheet surface could not be suppressed to a level that satisfies Equation 1a. As a result, the adhesion of the coating film decreased along with the decrease in chemical conversion treatment properties. In Comparative Example 30, it is thought that because the hydrogen concentration in the annealing process was low, S adsorbed on the surface of the cold-rolled steel sheet was similarly desorbed during the annealing process, which promoted the concentration of Sn on the steel sheet surface. Therefore, in the final steel sheet, it was not possible to have a large amount of S on the surface of the steel sheet at a level that satisfies Equation 2a, and related to this, the amount of Sn at a depth of 1 nm from the steel sheet surface I sn1 and the amount of Sn at a depth of 200 nm from the surface I sn2 The concentration of Sn on the steel plate surface could not be suppressed at a level that satisfied equation 1a. As a result, the adhesion of the coating film decreased along with the decrease in chemical conversion treatment properties.

[0089] In contrast, in all the examples, it is believed that by appropriately brush grinding the hot-rolled steel sheet to sufficiently remove the Sn-enriched areas on the surface of the hot-rolled steel sheet, and by applying an aqueous solution containing an S-containing compound to the surface of the cold-rolled steel sheet to sufficiently adsorb the S component from the S-containing compound onto the surface of the cold-rolled steel sheet, and by appropriately controlling the dew point and hydrogen concentration in the subsequent annealing process, the desorption of adsorbed S and the surface enrichment of Sn were suppressed. As a result, the surface S intensity I was observed in the analysis by X-ray fluorescence analysis. s1 and S strength I at the 1 / 4 plate thickness position s4 The equation satisfies equation 2a, and furthermore, the amount of Sn I at a depth of 1 nm from the surface in the analysis by XPS is sn1 and the amount of Sn at a depth of 200 nm from the surface I sn2 This allowed us to manufacture steel sheets that satisfy formula 1a, and significantly improved the adhesion of the coating film.

[0090] In particular, in Examples 2, 5, 12, 15 and 18, where the dew point in the annealing process was -50°C, sn1 / I sn2 is 2.0 or less and I s1 / I s4The ratio became 3.0 or higher, resulting in a coating adhesion rating of AA, indicating further improvement in coating adhesion. Similarly, in Examples 3, 6, 9, 16, 19, and 22, where the hydrogen concentration in the annealing process was 8% by volume, the coating adhesion rating was also AA for the same reason, indicating further improvement in coating adhesion.

[0091] In particular, in Examples 4, 7, 10, 13, 20, and 23, where the dew point in the annealing process was -50°C and the hydrogen concentration was 8% by volume, sn1 / I sn2 is 2.0 or less and I s1 / I s4 The ratio was 3.0 or higher, and furthermore, XPS analysis revealed that the amounts of Sn, C, O, Fe, Mn, Si, Cu, and Ni at a depth of 1 nm from the surface satisfied the condition Sn / (C+O+Fe+Mn+Si+Cu+Ni)≦0.007. As a result, the coating adhesion was evaluated as AAA, demonstrating a further improvement in coating adhesion.

Claims

1. In mass percent, C: 0.001 to 0.500%, Si: 0-3.00%, Mn: 0.10-3.00%, Al: 0.001-2.000%, Ni: 0.010 to 1.000%, Cu: 0.010-1.000%, Sn: 0.003-1.000%, P: 0.100% or less, S: 0.100% or less, N: 0.0150% or less, Ti: 0 to 0.150%, Nb: 0 to 0.150%, B: 0 to 0.0100%, Mo: 0-1.000%, Cr: 0-1.000%, V: 0 to 0.150%, W: 0-1.000%, Hf: 0 to 0.050%, Mg: 0 to 0.050%, Zr: 0 to 0.500%, Ca: 0-0.050%, REM: 0-0.010%, As: 0 to 0.100%, Ir: 0-1,000%, and Remainder: Fe and impurities It has a chemical composition containing, In analysis by X-ray photoelectron spectroscopy, the amount of Sn I at a depth of 1 nm from the surface was sn1 and the amount of Sn I at a depth of 200 nm from the surface sn2 The following equation 1a is satisfied, In analysis by X-ray fluorescence analysis, the surface S intensity I s1 and S strength I at the 1 / 4 plate thickness position s4 A steel plate characterized in that it satisfies the following formula 2a. I sn1 / I sn2 ≦3.0 ・・・1a I s1 / I s4 ≧2.0 ・・・2a

2. In the analysis by the X-ray photoelectron spectroscopy, the Sn content I at a position 1 nm deep from the surface sn1 and the Sn content I at a position 200 nm deep from the surface sn2 satisfies the following formula 1b, the steel sheet according to claim 1. I sn1 / I sn2 ≦2.0 ・・・1b

3. In the analysis by the aforementioned X-ray fluorescence analysis method, the surface S intensity I s1 and S strength I at the 1 / 4 plate thickness position s4 The steel plate according to claim 1 or 2, characterized in that it satisfies the following formula 2b. I s1 / I s4 ≧3.0 ・・・2b

4. The steel sheet according to claim 1 or 2, characterized in that, in the analysis by the aforementioned X-ray photoelectron spectroscopy, the amounts of Sn, C, O, Fe, Mn, Si, Cu, and Ni at a depth of 1 nm from the surface satisfy the following formula 3a. Sn / (C+O+Fe+Mn+Si+Cu+Ni)≦0.010...3a However, the amounts for Sn, C, O, Fe, Mn, Si, Cu, and Ni are expressed in units of at% for each element.

5. The steel sheet according to claim 4, characterized in that, in the analysis by the aforementioned X-ray photoelectron spectroscopy, the amounts of Sn, C, O, Fe, Mn, Si, Cu, and Ni at a depth of 1 nm from the surface satisfy the following formula 3b. Sn / (C+O+Fe+Mn+Si+Cu+Ni)≦0.007...3b However, the amounts for Sn, C, O, Fe, Mn, Si, Cu, and Ni are expressed in units of at% for each element.

6. The aforementioned chemical composition is, in mass%, Ni: 0.040-1.000%, Cu: 0.040 to 1.000%, and Sn: 0.004-1.000% A steel plate according to claim 1 or 2, characterized by including the following:

7. The steel plate according to claim 1 or 2, characterized by having a Vickers hardness of 190 Hv or higher.

Citation Information

Patent Citations

  • Hot rolled steel sheet having excellent chemical conversion treatability and method for manufacturing the same

    JP2003277959A

  • Method for producing high-tensile strength cold rolled steel sheet having excellent corrosion resistance after coating

    JP2007231311A

  • Structure steel and structure excellent in surface quality and coating corrosion resistance

    JP2021161459A

  • Martensitic stainless steel having excellent wear resistance and corrosion resistance, and method for producing same

    WO2015022932A1

  • Separator for solid polymer fuel cell and method for producing same

    WO2016129599A1